Cultural Heritage and International Law Objects, Means and Ends of International Protection (Springer International Publishing, 2018)
This book explores the objects, means and ends of international cultural heritage protection. It starts from a broad conception of cultural heritage that encompasses both tangible property, such as museum objects or buildings, and intangible heritage, such as languages and traditions. Cultural heritage thus defined is protected by various legal regimes, including the law of armed conflicts, UNESCO Conventions and international criminal law. With a view to strengthening international protection, the authors analyze existing regimes and elaborate innovative concepts, such as blue helmets of culture and safe havens for endangered cultural heritage. Finally, the ends of international protection come to the fore, and the authors address possible conflicts between protecting cultural diversity and wishes to strengthen cultural identity.